DIPG-07. GENOMIC ANALYSIS METHODS FOR IDENTIFICATION OF CANCER DRIVER PATHWAYS IN CHILDHOOD BRAIN TUMORS. Issue 2 (22nd June 2018) - Sanders, Lauren; Rose-Dey, Brittany; Beale, Holly; Pfeil, Jacob; Kephart, Ellen; Learned, Katrina; Durbin, Ann; Bjork, Isabel; Currie, Rob; Morozova, Olena; Agnihotri, Sameer; Salama, Sofie; et al.
Abstract: Diffuse intrinsic pontine glioma (DIPG) is a rare and invasive pediatric brain tumor with limited treatment options. The Treehouse Childhood Cancer Initiative at UC Santa Cruz has developed a comparative gene expression analysis method which identifies outlier genes in gene expression data from tumor samples. This method may be useful for identifying consistently activated pathways in difficult-to-treat tumors such as DIPG. We show here that this method can be used to identify HARS and HMGCR as over-expressed genes in a cohort of DIPG patient tumor samples. Differential expression analysis demonstrates that these genes are significantly over-expressed in DIPG tumors as compared to normal brain tissue, indicating that they may be therapeutically relevant. Targeting these genes in vitro with FDA-approved drugs significantly reduces cell line viability, and targeting both genes at once in combinatorial therapy is more effective than targeting each gene separately. Testing these drugs in human astrocytes and neural stem cells shows no reduction in cell viability. Pathway enrichment analyses demonstrate that the cholesterol biosynthesis pathway, which is driven by HMGCR expression and is a known driver pathway in gliomas, is enriched in DIPG cell lines and in DIPG patient samples. Our results indicate that the cholesterol biosynthesis pathway may be enriched in a subset of DIPG tumors and may be a viable therapeutic target. Future experiments will test our results on a larger cohort of DIPG cell lines.